PENDEKATAN KONTEMPORER DALAM RELIGIONSWISSENSCHAFT - Imam Iqbal (Religi: Jurnal Studi Agama-agama, 2018)
This paper discusses the approach commonly used in the discipline of Religionswissenschaft in contemporary periode. Here, the word “contemporary” refers more to the thought, rather than to the periodic chapter, as will be seen in the description of Frank Whaling, who specifically conducted a study of various contemporary approaches in this discipline. The study conducted by Whaling is a step that follows up with the study of Jacques Waardenburgh who previously mapped various classical approaches in this discipline.The discussion in this paper starts from the mapping that has been produced by the two experts. In addition, to obtain a more in-depth analysis of it, a number of other experts’ opinions were also stated. There are two core issues which are the main locus of the discussion in this paper, namely; first, about the emergence of the term contemporary approach, which is related to the background problem of its emergence and its fundamental differences with the classical approach; and second, about the implications for the development of the Religionswisschaft methodology, both practically and substantively. These two issues are explored descriptively and analytically to criticize and understand the existence of the problem in the midst of the great construction of the Religionswissenschaft.